2017
DOI: 10.1021/acs.est.7b01460
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol (SOA) from Nitrate Radical Oxidation of Monoterpenes: Effects of Temperature, Dilution, and Humidity on Aerosol Formation, Mixing, and Evaporation

Abstract: Nitrate radical (NO) oxidation of biogenic volatile organic compounds (BVOC) is important for nighttime secondary organic aerosol (SOA) formation. SOA produced at night may evaporate the following morning due to increasing temperatures or dilution of semivolatile compounds. We isothermally dilute the oxidation products from the limonene+NO reaction at 25 °C and observe negligible evaporation of organic aerosol via dilution. The SOA yields from limonene+NO are approximately constant (∼174%) at 25 °C and range f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 91 publications
15
100
5
Order By: Relevance
“…Recent chamber studies indicate a very low aerosol yield from α-pinene oxidation by NO 3 (Nah et al, 2016;Fry et al, 2014); the aerosol yield increases to ∼ 18 % when α-pinene is oxidized by OH (Rollins et al, 2010;Rindelaub et al, 2015). However, these results might not be representative of atmospheric conditions in terms of the RO 2 reaction partner or RO 2 lifetime, warranting further studies on the effects of RO 2 fates on aerosol formation (Boyd et al, , 2017Ng et al, 2008;Schwantes et al, 2015).…”
Section: Heterogeneous Loss Of Organic Nitratesmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent chamber studies indicate a very low aerosol yield from α-pinene oxidation by NO 3 (Nah et al, 2016;Fry et al, 2014); the aerosol yield increases to ∼ 18 % when α-pinene is oxidized by OH (Rollins et al, 2010;Rindelaub et al, 2015). However, these results might not be representative of atmospheric conditions in terms of the RO 2 reaction partner or RO 2 lifetime, warranting further studies on the effects of RO 2 fates on aerosol formation (Boyd et al, , 2017Ng et al, 2008;Schwantes et al, 2015).…”
Section: Heterogeneous Loss Of Organic Nitratesmentioning
confidence: 97%
“…Field and laboratory studies have indicated a potential contribution to the aerosol formation of organic nitrates from BVOC oxidation Fry et al, 2009Fry et al, , 2014Nah et al, 2016;Rollins et al, 2009;Rindelaub et al, 2015;Boyd et al, 2015Boyd et al, , 2017Lee et al, 2016;Ng et al, 2008;Xu et al, 2015;Lee et al, 2014;Bean and Hildebrandt Ruiz, 2016;Spittler et al, 2006). Aerosol yield depends on both the VOC precursor and the oxidant.…”
Section: Heterogeneous Loss Of Organic Nitratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of VOCs by the primary atmospheric oxidants, O 3 and q OH, C. Faxon et al: Characterization of organic nitrate constituents of secondary organic aerosol et al, 2016; Ng et al, 2017). Significant concentrations of these nitrates have been detected in the gas and condensed phases in both field and laboratory studies (Ayres et al, 2015;Beaver et al, 2012;Boyd et al, 2017;Bruns et al, 2010;Day et al, 2010;Fry et al, 2014;Lee et al, 2016;Nah et al, 2016;Paulot et al, 2009;Rindelaub et al, 2014Rindelaub et al, , 2015Rollins et al, 2012Rollins et al, , 2013Xu et al, 2016;Kiendler-Scharr et al, 2016). Organic nitrates (RONO 2 ) and organic peroxy nitrates (RO 2 NO 2 ), such as peroxy acetyl nitrate (PAN), may also form in the atmosphere (Roberts, 1990;Singh and Hanst, 1981;Temple and Taylor, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of NO3 59 with isoprene has a considerable SOA yield of 23.8% (Ng et al, 2008), and the reaction with 60 monoterpene, such as limonene, can reach 174% at ambient temperatures (Boyd et al, 2017). The 61 reactions of NO3+BVOCs are critical to the studies of aerosols on regional and global scales (Fry et 62 The heterogeneous hydrolysis of N2O5 produces soluble nitrate (HNO3 or NO3 -) and nitryl chloride 65 (ClNO2) on the chloride-containing aerosols (R4) (Finlayson-Pitts et al, 1989).…”
Section: No2 + No3 + M → N2o5 + M (R2) 49 N2o5 + M → No2 + No3 + M (Rmentioning
confidence: 99%